2012
DOI: 10.1007/s00253-012-4631-x
|View full text |Cite
|
Sign up to set email alerts
|

What do we know about the yeast strains from the Brazilian fuel ethanol industry?

Abstract: The production of fuel ethanol from sugarcane-based raw materials in Brazil is a successful example of a large-scale bioprocess that delivers an advanced biofuel at competitive prices and low environmental impact. Two to three fed-batch fermentations per day, with acid treatment of the yeast cream between consecutive cycles, during 6-8 months of uninterrupted production in a nonaseptic environment are some of the features that make the Brazilian process quite peculiar. Along the past decades, some wild Sacchar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
136
0
16

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(153 citation statements)
references
References 62 publications
1
136
0
16
Order By: Relevance
“…The high-density cell culture and simple composition of sugarcane juice allow a quick fermentation cycle (6-10 h) and low cell growth rates (Della-Bianca et al, 2013). The upstream steps include a sulfitation process, which enrich the downstream products with sulfur compounds, especially sulfate species (Della-Bianca et al, 2013). After fermentation, the fermented juice is processed into an ethanol stream and a liquid-rich by-product-vinasse.…”
mentioning
confidence: 99%
“…The high-density cell culture and simple composition of sugarcane juice allow a quick fermentation cycle (6-10 h) and low cell growth rates (Della-Bianca et al, 2013). The upstream steps include a sulfitation process, which enrich the downstream products with sulfur compounds, especially sulfate species (Della-Bianca et al, 2013). After fermentation, the fermented juice is processed into an ethanol stream and a liquid-rich by-product-vinasse.…”
mentioning
confidence: 99%
“…Effects of P PCK1 -RIM15 on alcoholic fermentation under more severe conditions The high viability of the P PCK1 -RIM15 cells after single-batch fermentation suggested that this strain may be beneficial for use in repetitive fermentation in which yeast cells are harvested after batch fermentation and reused in the next batch (8,9). To test this possibility, we repeated 7-day batch fermentation tests 10 times (70 days of fermentation in total) and measured carbon dioxide emission during the initial 3 days (E3) in the third (E3 3 ) and 10th (E3 10 ) cycles (Fig.…”
Section: Effectsmentioning
confidence: 99%
“…A loss-of-function mutation in Rim15p (rim15 5055insA ) found specifically in K7 and related strains (3) couples a decrease in stress tolerance with an increase in the fermentation rate through impairment of stress-induced anabolic synthesis of storage and structural carbohydrates and redirection of glucose into glycolysis (6). Stress-sensitive sake yeast strains are suitable for sake fermentation in which yeast cells are not subjected to severe osmotic stress due to the simultaneous saccharification and fermentation (SSF) process of rice starch (7) and are usually not recycled from one batch to another, unlike brewing of lager-type beer or production of bioethanol (8,9). However, to guarantee alcoholic fermentation under more stressful and/or repetitive fermentation conditions, other attempts should be made to control the activity of Rim15p, which plays pivotal roles in acquisition of stress responses (10e13) and inhibition of alcoholic fermentation (3,6,14e16).…”
mentioning
confidence: 99%
“…Contrariwise, some isolates were found to derive from genetic modifications, a clonal differentiation that occurs during the fermentation process. This mainly occurs due to the unique large-scale fed-batch process, which utilizes acid cell recycling and submits the cells under a great deal of stress (Della-Bianca et al, 2013). Yeast isolates subjected to harsh conditions tend to develop genetic-induced physiological traits that make them more resistant, including the activation of genes responsible for cell wall integrity and oxidative stress response (Elsztein et al, 2011).…”
Section: Discussionmentioning
confidence: 99%